The Survival of Finnish and Karelian Tradition Today - CORRADI, CARLA (Reguly Társaság, 2011)
Ancient tradition in Finland and Karelia survives in many forms. The Permanent Laboratory of Shamanic Studies of the University of Bologna has for some time dedicated a branch of research to the methods of conservation of these ancestral beliefs, with particular reference to the transmission of popular literature and to the fortune of the Kalevala and ancient mythology in today’s culture. It is still possible to find narrators of the ancient fables and singers of popular poetry which are rich in mythological and symbolic elements related to the vision of the world of the ancestors. There are those in Finland who are concerned with preserving this cultural patrimony of inestimable worth through its transcription or those who make it known by transferring it to the stage. The themes of the Kalevala are still present and are to be found in contemporary literature and art. It is significant that the Lappish-Finnish writer Arto Paasilinna considers his “novels” a kind of continuation of the Finnish national poem. His stories contributed to the keeping alive, even through irony, of the original mythical and magic scenario and the relative symbolism of shamanic stamp. Furthermore, paintings, theatrical representations and musical compositions, including rock and folk groups, which are famous at an international level, are connected with the Kalevala. There are even those who state that Finnish rock music was born out of the national epic. Among the initiatives of artists who contribute to the maintenance of the vitality of the ancient pantheon is that of Lea Turto who in 2005 covered with red felt the stumps and roots of eleven trees in the Central Park of Helsinki to honour Hiisi, the spirit of the woods. In the daily life of the Finns too, the ties with mythology are still alive: surnames, the names of public institutions, streets and place-names bear witness to the permanence of their ancient culture which is the expression of their national identity.